Private Sector Participation in Child Health : A Review of World Bank Projects, 1993-2002 - Axelsson, Henrik; Bustreo, Flavia; Harding, April (World Bank, Washington, DC, 2013)
There is an increasing amount of evidence to support the view that the private sector significantly influences child health and nutrition outcomes through both service provision and supply of health related goods. In this context, this paper analyzes World Bank projects in Health, Nutrition and Population between fiscal years 1993-2002. The paper identifies the range of approaches taken to involve the private sector in improving child health outcomes; the actors involved; the type of activities supported by the projects; and examples of successful private sector participation. The paper's concludes: As measured by the proportion of projects (more than 50 perccent) that involved the private sector in child health, private sector participation was significant. As measured by the magnitude of involvement (budget amounts and stated project objectives), the degree of private sector participation was relatively small for most projects. Since most projects did not mention a systematic assessment of potential and opportunities to engage the private sector, it was difficult to assess whether or not engagement of the private sector was intentional. It was not possible to analyze how and if private sector participation resulted in better health for children, as private sector monitoring indicators measured process and not outcomes. The paper recommends: Encourage engagement of the private sector in World Bank projects addressing child health outcomes. Increase support to World Bank staff and its clients, for example through manuals or toolkits and field demonstrations of successful strategies to engage the private sector in child health programs. Conduct systematic assessments of the potential of the private sector to contribute to improved child health programs. Develop indicators that can measure which approaches lead from private sector engagement to better health for children. Incorporate mechanisms, such as health insurance, risk sharing, subsidies and targeted public health expenditures, to protect the poor and ensure that they are not further impoverished due to payments for health care services.